Correlation Among Inhibin A And B, Anti-M ¨Ullerian Hormone, Follicle-Stimulating Hormone, Luteinizing Hormone, And Estradiol Hormones In Infertile Women - Aytan Ali, Abdullayeva; Fazil Kurbanova, Jamila (Journal of Medical Biomedical and Applied Sciences, 2018)
Objective: The main purpose of this study was to assess ovarian reserve in infertile women and whether hormonal status depends on anti-M¨ullerian hormone level.Study Design: This retrospective study evaluated and compared inhibins A and B, follicle-stimulating hormone, luteinizing hormone, and estradiol concentrations in 67 infertile women with anti-M ¨ullerian hormone level <600 ng/L and in 39 infertile women with anti-M¨ullerian hormone level >600 ng/L. Data were analyzed using SPSS version 20 (IBM, Armonk, NY, USA) and reported as mean±standard deviation or number and percentage. The data in the study groups were nonparametric.Results: The mean concentrations of inhibin A and B and estradiol levels were lower (p<0.05) in infertile women with low anti-M¨ullerian hormone level. Serum inhibin A level (p<0.01) positively correlated with inhibin B level in women with anti-M¨ullerian hormone level <600 mg/mL. In women with anti-M¨ullerian hormone level >600 mg/mL, negative correlations were found between inhibin A and B levels (r=0.494, R2=0.13, p<0.01) and between anti-M¨ullerian hormone and inhibin B levels (r=-0.426, R2=0.149, p<0.01), but a positive correlation was demonstrated between inhibin A and anti-M¨ullerian hormone levels (r=0.545, R2=0.096, p<0.01). The analyses of correlations between follicle-stimulating hormone and estradiol showed a major coefficient of correlation (r=0.545, R2=0.287, p<0.05). There was no correlation between age and anti-M¨ullerian hormone.Conclusion: Differences in correlation between inhibin A and B levels in groups with different anti-M ¨ullerian hormone levels demonstrate their importance in the evaluation of ovarian reserve in infertile women. Hence, we conclude that ovarian reserve assessment in infertile women should include not only the anti-M ¨ullerian hormone level bwut also the inhibin A and B levels.